A review on extraction, purification, structural characteristics and bioactivities of polysaccharides from Polygonatum odoratum (Mill.) Druce. (May 2022) - Zong, Xin-Yan; Xu, De-Chang; Yin, Jun-Yi; Nie, Shao-Ping; Xie, Ming-Yong
Abstract: Polygonatum odoratum (Mill.) Druce is one of famous traditional Chinese medicines (TCM), which has been used as medicines and edible food. There are various bioactive substances in Polygonatum odoratum, including carbohydrate, amino acid, vitamin and protein. Polysaccharide is one of the main bioactive substances, which exhibits physiological benefits and nutritional functions. In this paper, the extraction, purification, structural characteristics and functional activities of polysaccharide from Polygonatum odoratum are summarized, which would provide a reference for its development and utilization.